2022
DOI: 10.3390/foods11081105
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition and Bioactive Compounds of Basil, Thyme and Sage Plant Additives and Their Functionality on Broiler Thigh Meat Quality

Abstract: Meat industries across the world are constantly focusing to find natural low-cost additives for the development of novel meat products to meet consumer demand for improving the health benefits. In this study, we investigated the chemical composition and the bioactive compounds of some herbal plants, namely basil, thyme, sage, and their functionality on broiler chicken thigh meat quality. Chemical composition, as well as total antioxidant activity, polyphenols, vitamin E lutein and zeaxanthin and the fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…However, varying results have been reported on their effects on overall broiler production performance [ 1 , 5 ]. There was no agreement between previous studies about the effects of thyme or oregano essential oils on feed intake, body weight gain, and feed conversion in broilers when these oils were used separately [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, varying results have been reported on their effects on overall broiler production performance [ 1 , 5 ]. There was no agreement between previous studies about the effects of thyme or oregano essential oils on feed intake, body weight gain, and feed conversion in broilers when these oils were used separately [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 55%
“…Some studies reported positive effects on the performance parameters of broiler chicks [ 8 , 11 , 12 ], while other studies showed no effect on broiler performance parameters [ 13 , 14 ]. In contrast to these studies, others reported negative effects of supplemental thyme or oregano oils in rations on broiler growth [ 6 , 7 , 15 ]. The use of thyme with prebiotics, such as mannan-oligosaccharides, in the feed formulation showed positive effects on the growth performance of broilers [ 16 ].…”
Section: Introductionmentioning
confidence: 98%
“…However, EPA-enriched eggs are harmful to infants, due to their competition with arachidonic acid (C20:4 n-6) for incorporation into tissue phospholipids [ 39 ]. Another logical explanation is that due to elongation and desaturation, EPA was converted entirely into DHA in the hens’ livers, however, this process was not observed in chicken’s thigh meat, where EPA was determined [ 40 ]. A similar phenomenon was also observed by others when EPA was largely converted into DHA [ 41 , 42 , 43 ] when laying hens were fed flaxseed-based diets.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, comparing the average percentages of the individual FAs, the results were similar for palmitic (16.2 and 20.6%), linolenic (69.0 and 54.7%) and linoleic acid (9.7 and 10.4%), where the second value in the bracket represents the average value found in the present study. On the contrary, in the study conducted by Vlaicu et al [ 12 ] the most abundant fatty acids were SFAs followed by PUFAs and MUFAs (40.5, 36.6 and 21.9%, respectively), with palmitic and linoleic acids having comparable values (23.0 % and 17.4%, respectively) and linolenic acid having a much lower percentage (15.9%) as compared to the study reported by Tarchoune et al [ 11 ] (69.0%) and to ours (54.7%). The different way samples have been prepared in the mentioned studies do not allow to establish the reason for the different FA composition found.…”
Section: Resultsmentioning
confidence: 86%
“…Fatty acid (FA) composition of the extract is important when considering the potential of an herb from the nutritional, nutraceutical, cosmetic or several other applicative points of view. To the best of our knowledge, only Tarchoune et al [ 11 ] and, more recently, Vlaicu et al [ 12 ] reported on the FA composition of basil leaves. In the first study, EO and FA compositions were evaluated.…”
Section: Introductionmentioning
confidence: 99%